An Assessment of Service Quality in Private Higher Education Sector with Respect to Students’perceptions - Fatima, Shaheen; Ahmad, Aqeel; Fatima, Samreen (International Journal of Psychosocial Rehabilitation, 2020)
Universities are the breeding grounds of societies having intellectuals and knowledge capital. Ratio of private higher education institutions of Pakistanis increasing since 2010. The current study attempts to measure determinants of service quality by students’ perceptions perspective in most and least influential factors.Private sector HEIs of Pakistan is the population area, particularly Lahore.As far as service quality of private sector HEIs is concerned this study directs areas for improvements. By following a quantitative approach, data was collected using questionnaire having five dimensions of service quality and 48 items. Ten private sector HEIs were included in study as sample. TheCronbach Alpha used for this instrument was 0.910 for all the dimensions of service quality. Exploratory factor analysis was used which extracted nine factors as determinants of service quality of HEIs with students’ perception perspective. Principal component Analysis, Rotated Component Matrix elaborates those eight ineffective items which are not converge in ninefactors. Recommendations are provided to improve service quality in those ineffective items of service quality. The study was limited to private higher education sector of Lahore and students’ perception aspect of service quality was considered only. Further researchers can study on government higher education sector by considering various stakeholders perspective of service quality.